Contemporary issues in management - Ahmad, Mohammad Saif (Journal of Management and Science, 2013)
Millions of men and women spend their time as managers in diverse organizations and are confronted by complex challenges as they perform their routine functions. Removal of trade restrictions, privatization and integration of national economies with the world economy have made jobs of managers and employees more challenging as well as rewarding. As a growing social discipline, management theories and practices have also undergone a sea-change. As obvious, a large number of management gurus have been contributing towards the development of management theories but unfortunately many contributors were over shadowed by others in their life time. The world recognized their contributions only decades after their death. The scientific theory of management developed by Taylor and, of course, by others dominated for most of the twentieth century. But by the late 1980s, most of the assumptions held by experts as valid, became obsolete. According to P.F. Drucker, father of 20th century modern management, neither individuals nor organizations can be successful if they stick with the old assumptions just as the horse and carriage can no longer compete with the automobile.